Pelayanan Pendaftaran Tanah Sistematis Lengkap (PTSL) Terhadap Kepuasan Masyarakat Pada Badan Pertanahan Nasional Kabupaten Bekasi - nurhidayati nurhidayati; Rani Silpia (Universitas Bina Sarana Informatika, 2018)
The National Land Agency (BPN) is a Government Institution established to assist the society in the management of land rights. To facilitate service to the society, BPN has a Complete Systematic Land Registration Program (PTSL). The purpose of this study was to determine the effect of Complete Systematic Land Registration Service (PTSL) on society satisfaction in the Bekasi District National Land Agency. The researchers use descriptive quantitative research methoyds using SPSS 22.0 application. The research sample was taken in non probability sampling, specifically purposive sampling, on 47 respondents by distributing questionnaires. The analysis used was the correlation coefficient test method, determination and regression equation. The results of the calculation, the correlation value of 0.532 which means that there is a strong relationship between public service to socie satisfaction at the BPN Office, the coefficient of determination is 2.83% and the remaining 71.7% is influenced by other factors and the regression equation of Y = 5.956 + 0.799X which means if public service = 0, then community satisfaction is 5,956 and every additional public service 1% will increase community satisfaction by 0,799. After the hypothesis is tested, Ha is accepted and H₀ is rejected as a public service has an influence on society satisfaction at the Bekasi District BPN Office.